Influence of rectangular steel splice-sleeve for precast concrete connection - Abd. Rahman, Ahmad Baharuddin (Penerbit UTM Press, 2015)
Precast concrete building system has gained its popularity in Malaysia because of the many advantages such as high quality of structural components, less labour intensive at the construction site, and shorter completion time of a project. One of the constraints in precast concrete structures is to ensure that the connections are strong enough to ensure the structural integrity and robustness of the overall frames. In this study, a total of nine rectangular steel splice-sleeve connections were tested experimentally under incremental tensile loads. Two steel plates were inserted and welded to each end of the steel splice-sleeve. The steel plates act as shear key to provide the interlocking mechanism to the grout and to enhance the bond property between the grout and the splice. These plates were adopted to prevent the grout slippage from the sleeve. The grout strength, embedded steel bar lengths and the size of the steel sleeve splice were varied among the specimens to study their effect on the tensile performance of the connection. The results showed that the higher strength of grout, longer embedded length of steel bar and smaller size of the sleeve contributes to a higher ultimate tensile load.